Heat transfer enhancements in a concentric double pipe exchanger equipped with swirl elements - Akpinar, EK; Bicer, Y; Yildiz, C; Pehlivan, D (Pergamon-Elsevier Science Ltd, 2004)
The effect of had transfer rates of swirl ganarators with holes for the entrance of fluid were investigated by placing than at the entrance section of inner pipe of heat exchanger. Various swirl generators having different arrangements of holes were used. Hot air and cold water were passed through the inner pipe and annulus respectively. Experiments were carried out for both parallel and countercurrent flow models of the fluids at Reynolds numbers between 8500-17500. The results showed that up to 130% enhancement could be accomplished in beat transfer rates with this kind of swirl generators compared to beat exchanger without these elements. (C) 2004 Elsevier Science Ltd.
Keywords: Circular Pipe; Fluid-Flow; Tube